2021
DOI: 10.3390/ijms222111813
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analyses Reveal Metabolites Affected by Plant Growth-Promoting Endophytic Bacteria in Roots of the Halophyte Mesembryanthemum crystallinum

Abstract: Mesembryanthemum crystallinum L. (common ice plant) is an edible halophyte. However, if ice plants are used to phytoremediate salinity soil, there are problems of slow initial growth, and a long period before active NaCl uptake occurs under higher salinity conditions. Application of endophytic bacteria may improve the problem, but there remain gaps in our understanding of how endophytic bacteria affect the growth and the biochemical and physiological characteristics of ice plants. The aims of this study were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Elevated soil salinity is yet another serious worldwide problem caused by excessive human activities such as deforestation, improper irrigation and fertilization ( Ashraf et al, 2010 ; Liang et al, 2017 ). Approximately 20% of irrigated areas are affected with salinization caused by irrigation not only with seawater but also with water considered as good quality, which may still contain up to 500 mg⋅dm –3 of soluble salts ( Zhang et al, 2018 ; Kataoka et al, 2021 ). Salinity is regarded as a common primary cause of stress in plants leading to increased osmotic pressure and water deficit, nutritional imbalance and accumulation of toxic ions in plant organs, mostly roots, and has strong negative influence on plant growth and development ( Zanetti et al, 2019 ; Nosek et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Elevated soil salinity is yet another serious worldwide problem caused by excessive human activities such as deforestation, improper irrigation and fertilization ( Ashraf et al, 2010 ; Liang et al, 2017 ). Approximately 20% of irrigated areas are affected with salinization caused by irrigation not only with seawater but also with water considered as good quality, which may still contain up to 500 mg⋅dm –3 of soluble salts ( Zhang et al, 2018 ; Kataoka et al, 2021 ). Salinity is regarded as a common primary cause of stress in plants leading to increased osmotic pressure and water deficit, nutritional imbalance and accumulation of toxic ions in plant organs, mostly roots, and has strong negative influence on plant growth and development ( Zanetti et al, 2019 ; Nosek et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…No significant toxic effect is visible up to 40% of salt content in plant dry mass ( Amari et al, 2014 ). That unique feature makes the common ice plant a perfect model in saline phytoremediation ( Kataoka et al, 2021 ). In turn, Ghnaya et al (2005) first suggested that it may also be a perfect candidate in cadmium decontamination due to accumulation capabilities of considerable amounts of this element in tissues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations